Heterogeneity in migrating neural crest cells revealed by a monoclonal antibody - Barbu, M (J Neurosci, 1986)
A monoclonal antibody, GlN1, obtained by immunization with extracts of the 14 d embryonic quail nodose ganglion, is described. GlN1 recognizes an antigenic determinant present in virtually all the satellite cells of the peripheral ganglia, all Schwann cells of the peripheral nerves, and in subpopulations of sensory and autonomic neurons of embryonic and adult quails and chickens. The molecular weight of the antigen(s) revealed by GlN1 in embryonic day 12 quail dorsal root ganglion (DRG) cultures is around 80 kDa. In the neural crest, GlN1 determinant is found as soon as the crest cells leave the neural primordium. Only a proportion (25%) of the migrating neural crest cells carry the antigen. This demonstrates that the neural crest is composed of a heterogeneous population of cells from its early migratory stages. Being selectively distributed on neural crest cells and its derivatives, the GlN1 determinant may be considered as a “differentiation antigen” that will be useful in further studies on cell-line segregation during the ontogeny of the PNS.